Phoenix: Towards Designing and Developing a Human Assistant Rover - Akib Zaman; Mohammad Shahjahan Majib; Shoeb Ahmed Tanjim; Shah Md. Ahasan Siddique; Fardeen Ashraf; Shafayetul Islam; Abu Hena Md. Maruf Morshed; Shadman Tajwar Shahid; Ishraq Hasan; Oliullah Samir; Safwan Shafquat; Naim Ibna Khadem Al Bhuyain; et al. (IEEE Access)
Human-assistance rovers have a broad prospect in the field of space robotics, as a significant number of organizations and researchers have been investing in the design and development of sophisticated rovers for planetary exploration. In order to promote research and development in the design of next-generation MARS rovers, an annual University Rover Challenge (URC) is hosted by the MARS Society in the United States. In this study, we highlight the design and development process of several novel subsystems of a human-assistance planetary exploration rover and their successive integration in the prototype named PHOENIX, which is a rover that participated in the URC 2021. First, a detailed requirement elicitation has been conducted, for designing a conceptual framework for a rover capable of planetary exploration. Secondly, the design and development process has been detailed for five basic subsystems (power, communication, primary-manipulator, chassis with drive, processing) and two mission-specific subsystems (scientific exploration and autonomous navigation), as well as their successive integration into the rover. Afterwards, a detailed evaluation study has been conducted in order to validate the performance of the developed system. Terrain traversability, autonomy in navigation, and sophisticated task execution capabilities have been evaluated individually within this study. Additionally, the capability of the rover in detecting bio-signatures from soil samples using a novel Multiple Bio-molecular Rapid Life Detection (MBLDP-R) protocol has also been evaluated. The developed scientific exploration subsystem is capable of detecting the presence of life from soil samples with a 92% success rate, and from rock samples with a success rate of 93.33%.